God's grace exposition of Bible doctrines, taking the epistle to the Romans as a point of departure - Barnhouse, Donald Grey, 1895-1960 (London, UK Pickering and Inglis, 1959)
Includes index.
Donated by Mr C. Clack.
Keywords: Bible. N.T. Romans V -- criticism, interpretation, etc; Bible. N.T. Romans V -- theology; Grace (theology) -- biblical teaching